Сomputer-oriented learning of differential equations by Bachelors of Information Technology - Sitak, I. V. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with didactic approaches to the use of computer-oriented support differential equations mastering for the future Bachelors of Information Technology. The author analyzed the approaches of the Ukrainian scientists to the definition of computer-oriented technologies and identifies the differences between the concepts of "information and communication technologies" and "computer-oriented technologies." Analysis of the main didactic possibilities of the researched learning technologies gave an opportunity to find out the possibility of using computer-oriented support differential equations mastering for the future Bachelors of Information Technology, namely the use of software designed for demo simulation, to provide component activity-object-oriented environment, determine the level of educational achievements of students , obtain reference messages. It is concluded that it is appropriate to place a training course on differential equations on the website for more efficient training. The author analyzes the content of existing online resources that provide blended learning differential equations of the future professionals and proposes computer-oriented tools to accompany the stages of formation actions of Bachelors of Information Technology during the study of differential equations.